Ensuring competitiveness and economic security of a developer in unstable conditions: financial stability, adaptability, innovation - BIELIENKOVA, Olha; Kyrylov, Ihor; STROYENKO, Anna (Ways to Improve Construction Efficiency, 2025)
The article is devoted to a comprehensive study of mechanisms for ensuring the competitiveness of development companies in conditions of high instability caused by military actions, transformation of the economic environment and changes in investor behavior. The paper substantiates that traditional approaches to managing development projects no longer provide sufficient stability, and competitiveness is formed through the integration of three interrelated components: financial stability, adaptability and innovation. The strategies of development companies operating in the Kyiv market are analyzed. The key features of successful adaptive strategies are identified, and a comparison is made with the strategies of companies that significantly reduced their activities during the war. An approach to ensuring the competitiveness of developers in the market through a combination of financial stability, adaptability and innovation is proposed. Financial stability is considered a key factor in the survival of companies in a period of sharp increase in risks, when liquidity, solvency, transparency, cost control and diversification of financing sources are of critical importance. It is determined that the developer’s ability to fulfill obligations to investors builds trust in the brand and significantly increases its market position. Adaptability is defined as the ability of companies to quickly restructure business processes, adjust the project portfolio, change architectural and technological solutions, and respond to new requirements of buyers regarding security, autonomy and energy efficiency of housing. It is shown that flexible management models allow minimizing losses and ensuring prompt resumption of activities. Innovation is considered in terms of the implementation of digital solutions, automation, BIM technologies, modern construction control systems, as well as the transition to new formats of communication with investors and increasing the transparency of processes. It is proven that innovations create added value for consumers and provide long-term competitive advantages. The article emphasizes that the synergy of financial stability, adaptability and innovation forms a new strategic model for the development of development companies, capable of ensuring not only survival in the crisis period, but also sustainable growth in the post-war perspective.